PROCESS OF QUALITY EDUCATION AS A MECHANICAL SUM OF TEACHING AND LEARNING PROCESSES - M. Botirova Mukarramkhan Moydinovna (Web of Journals Publishing, 2023)
This article is focused on elucidating the concept of "Educational Process", directly related to any educational institution, such as educational process, education, education, all-round development. In this process, students' personal qualities are formed and developed. The main task of the educational process is the discovery of new scientific truths.
Keywords: Education, education, student, knowledge, development , personality.